A natureza perfeita na Serra Monte Cristo - Gomes , Daura Janes; Lourdes r, Dayane Freitas de; Ferreira, Edna; Henrique , Luiz; Ferreira , Luciana Lopes; Castilho , Mery Terezinha; Carraro, Márcia Regina Simpioni (REVISTA PROGRAMA A UNIÃO FAZ A VIDA_____________________________________________________________________________________________________________, 2021)
>>> ver pdf